Incisor bone osteosynthesis in a Colombian Creole horse: Case report - Bedoya Ríos, Miguel Ángel (2022)
It is reported the case of a 7-year-old Colombian Creole horse that was admitted to the Large Animal Veterinary Clinic of the Universidad Cooperativa de Colombia. In the clinical evaluation, the fracture of the incisor bone was determined. It was corrected through the restoration technique using a wire anchorage or interdental wiring of the incisors (cerclage technique). The patient presented a satisfactory evolution showing a consolidation of the fracture without complications of malocclusion. The implemented procedure was relatively simple and provided welfare to the equine.